A Survey on Cloud Computing with different Encryption Techniques to Secure Cloud Data - Prajapati, Kiran; choudhary, Jaytrilok (International Journal of Computer Sciences and Engineering, 2015)
Cloud provides facility of assigning data to a great number of scattered computers, rather than local computer or remote server. This paper briefly surveys the issues in cloud computing security. The fact is that the data shared with the cloud service provider is identified as the core scientific problem that separates cloud computing security from other topics in computing environment. The paper also describes different encryption techniques to secure the cloud data from unauthorized users.